Phenotypic and Molecular Characterization of Carbapenem-Heteroresistant Bacteroides fragilis Strains - Zain Baaity; Friederike D. von Loewenich; Elisabeth Nagy; László Orosz; Katalin Burián; Ferenc Somogyvári; József Sóki (MDPI AG, 2022)
Carbapenem-resistant Bacteroides fragilis strains usually emerge by an insertion sequence (IS) jump into the upstream region of the cfiA carbapenemase gene. However, intermediate or fully resistant cfiA-positive strains also exist. These do not have such IS element activations, but usually have heterogeneous resistance (HR) phenotypes, as detected by a disc diffusion or gradient tests. Heteroresistance is a serious antibiotic resistance problem, whose molecular mechanisms are not fully understood. We aim to characterize HR and investigate diagnostic issues in the set of cfiA-positive B. fragilis strains using phenotypic and molecular methods. Of the phenotypic methods used, the population analysis profile (PAP) and area under curve (AUC) measurements were the best prognostic markers for HR. PAP AUC, imipenem agar dilution and imipenemase production corresponded well with each other. We also identified a saturation curve parameter (quasi-PAP curves), which correlated well with these phenotypic traits, implying that HR is a stochastic process. The genes, on a previously defined 'cfiA element', act in a complex manner to produce the HR phenotype, including a lysine-acetylating toxin and a lysine-rich peptide. Furthermore, imipenem HR is triggered by imipenem. The two parameters that most correlate with the others are imipenemase production and 'GNAT' expression, which prompted us to suspect that carbapenem heteroresistance of the B. fragilis strains is stochastically regulated and is mediated by the altered imipenemase production.